The Spatial Distribution Characteristics and Driving Factors of Traditional Villages’ Tourism Transformation Level in Shaanxi, China - Jia, Huidi; Li, Lanbo; Wu, Siying; Zhao, Ruiqi; Yang, Huan (Land (Basel), 2025)
Although numerous studies have examined the spatial patterns of traditional villages and their driving factors, limited attention has been devoted to the transformation of tourism. This study focused on traditional villages in Shaanxi Province, employing geodetector and grounded theory methods to analyze their spatial distribution characteristics and influencing factors. First, most traditional villages have not developed tourism. Only 11.98% reached the relatively mature tourism stage. Second, the spatial distribution of mature traditional tourism villages is scattered and primarily clustered in Liuba County, Mizhi County, and Jia County. Third, the factors influencing spatial distribution characteristics include resource endowment, transportation accessibility, and regional economic conditions. Among these factors, the level of traditional villages, village heritage values, and the local tourism environment show the strongest explanatory power. These findings can help enhance cultural resilience, promote economic transformation and upgrading, and support the sustainable development of traditional villages.